Aplikasi Pemupukan Berimbang untuk Peningkatan Laju Pertumbuhan Tanaman Gaharu (Gyrinops verstegii) di Kabupaten Tabanan - KETUT DHARMA SUSILA; I MADE MEGA (Fakultas Pertanian Universitas Udayana, 2012)
The research that purposed to find out the combination dosage of balanced fertilizing betweenunorganic and organic fertilizers for growth rate increasing of gaharu was conducted at West MundehVillage, West Selemadeg District and Baturiti Village Kerambitan District, Tabanan Regency from August2006 until August 2007. The factorial experiment used was randomized block design consisted of twofactors namely organic fertilizers as the first factor with four levels: 0 kg bokashi/tree; 2.5 kg bokashi/tree; 5.0 Kg bokashi/tree; 7.5 kg bokashi/tree; and unorganic fertilizer (NPK fertilizers) as a secondfactor with four levels: without NPK; 0.10 kg NPK/tree; 0.20 kg NPK/tree, and 0.30 kg NPK/tree.There were 16 treatments with 4 replications. The result showed that no interaction between organicand unorganic fertilizer treatments, however, each factors influenced growth rate increasing of gaharuindividually. Both organic (bokashi) and unorganic fertilizers (NPK) were increasing the stem diametersand hight of plants gaharu. Treatments of 0.30 kg NPK/tree and 7.5 kg bokashi/tree indicated betterperformance significantly for raising stem diameter than the others.